Effects of setup of centralized biogas plants on crop acreage and balances of nutrients and soil humus - Moller, Kurt; Muller, Torsten; Schulz, Rudolf (Nutrient cycling in agroecosystems, 2011)
An increasing number of biogas plants (BGPs) based on digestion of dedicated energy crops have been implemented in Germany. The objectives of this study were to assess the changes in (1) the acreage of different crops (silage maize, cereals, etc.) related to the setup of the BGP, (2) nutrient flows and budgets (N, P, K) due to the implementation of the BGPs, and (3) to assess the effluent N in the overall crop N supply. Data from 14 farmers before the setup of the BGPs were compared with data after implementation. Due to the setup of the BGPs, the acreage of silage maize greatly increased and there were significant negative effects on the weighted soil humus budgets, no effects on the weighted mean N and P budgets, and a negative trend regarding the K budgets. Results concerning the N release from organic manuring to maize crops showed that one third of the farmers considerably over-fertilize maize, indicating an underestimation of short- and long-term N supply of manure N. The implementation of centralized BGPs established very intensive nutrient cycles and, in the long-term higher risks of nutrient losses and environmental pollution are expected. One very effective measure to compensate for negative effects on the soil humus budgets and nitrate leaching is an enlargement of cover cropping, which will also offer economic revenue by providing aboveground biomass for digestion. If the amounts of effluents returned to a single farm or field are not adapted to the nutrient composition of the substrates delivered to the BGP, large nutrient imbalances can result. An effective measure to get a better allocation of the available nutrients is a solid-liquid separation of the effluents, enabling a more targeted allocation of the nutrients.